Development and Its Applications in Scientific Knowledge 2023
DOI: 10.56238/devopinterscie-156
|View full text |Cite
|
Sign up to set email alerts
|

Teaching about medicinal plants at school: Following in the footprints of Frei Veloso

Abstract: Brazil is home to the richest, most important and diverse flora in the world. This fact reveals the great plant potential of the country in the development of medicines, cosmetics, nutraceuticals and other innovative products (NEWMAN & CRAGG, 2012). In addition to the vast biodiversity, Brazil also has a rich socio-diversity, built over the centuries by the miscegenation of Amerindian, African and European cultures (VALLI & BOLZANI, 2019). However, despite its recognized potential, native vegetation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Taking into account the pre-test score of 29 and post-test scores of 87, it is observed that the results of this study overlap with Kassimbekova et al (2021). Similarly, Brandão et al (2023) emphasized the importance of medicinal plants and the necessity of teaching them to students in their study "Teaching Medicinal Plants at School: In the Footsteps of Frei Veloso". When the literature is examined, it is seen that the studies are aimed at application in medical gardens and educational gardens (Reyes 2021;Osma, Guapacha and Saavedra 2016).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Taking into account the pre-test score of 29 and post-test scores of 87, it is observed that the results of this study overlap with Kassimbekova et al (2021). Similarly, Brandão et al (2023) emphasized the importance of medicinal plants and the necessity of teaching them to students in their study "Teaching Medicinal Plants at School: In the Footsteps of Frei Veloso". When the literature is examined, it is seen that the studies are aimed at application in medical gardens and educational gardens (Reyes 2021;Osma, Guapacha and Saavedra 2016).…”
Section: Discussionmentioning
confidence: 66%
“…Ön testlerinde yüksek yeterlilik düzeyine sahip birey sayısı kontrol grubunda 9, deney grubunda 8'dir. Son testlerde bu sayı kontrol grubunda 12'ye, deney grubunda ise 15'e yükselmiştir.Benzer şekildeBrandão et al (2023) "Okulda Tıbbi Bitkilerin Öğretilmesi: Frei Veloso'nun İzinde" çalışmasında tıbbi bitkilerin önemini ve öğrencilere öğretilmesinin gerekliliğini vurgulamışlardır. Makalede, tıbbi bitkilerin insan sağlığı, ekonomi ve çevre için önemli bir yere sahip olduğu belirtilmektedir.…”
unclassified